Standardized assessment of cognitive function, mood, and pain among patients who are unable to communicate. Issue 4 (2nd March 2022) - Shier, Victoria; Edelen, Maria O.; McMullen, Tara L.; Dunbar, Michael S.; Bruckenthal, Patricia; Ahluwalia, Sangeeta C.; Chen, Emily K.; Dalton, Sarah E.; Paddock, Susan; Rodriguez, Anthony; Mandl, Stella; Mota, Teresa; et al.
Abstract: Background: Assessments of patients have sought to increase the patient voice through direct patient interviews and performance‐based testing. However, some patients in post‐acute care (PAC) are unable to communicate and cannot participate in interviews or structured cognitive tests. Therefore, we tested the feasibility and reliability of observational assessments of cognitive function, mood, and pain for patients who are unable to communicate in PAC settings. Methods: We conducted a national test of observational assessments of cognitive function, mood, and pain in 143 PAC facilities (57 home health agencies, 28 Inpatient Rehabilitation Facilities, 28 Long‐Term Care Hospitals, and 73 Skilled Nursing Facilities) across 14 U.S. markets from November 2017 to August 2018. For the 548 patients identified as unable to make themselves understood, we assessed descriptive statistics, percent of missing data, time to complete, and inter‐rater reliability (IRR) between paired research nurse and facility staff assessors. Results: Most sampled non‐communicative patients were administered all three observational assessments. Among assessed patients, overall missing data was high for some items within the Staff Assessment for Mental Status (2.9% to 33.5%) and Staff Assessment of Patient Mood (12.4% to 44.3%), but not the Observational Assessment of Pain or Distress (0.0% to 4.4%). Average time to complete the data elements ranged from 2.4 to 3.5 min and IRR was good to excellent for all items (kappa range: 0.74–0.98). Conclusion: The three observational data elements had acceptable reliability. Although results revealed varying feasibility, there was support for feasibility overall in terms of implementing a standardized observational assessment of pain for patients in PAC settings. Additional work is needed for the Staff Assessment for Mental Status and the Staff Assessment of Patient Mood to improve the observable nature of these data elements and enhance instructions and training for standardizing the assessments.